Let P=(cosA sinA)

(sinA cosA)
Q=(cosB sinA)
(sinB cosA) show that
PQ=(cosA(A-B) sin(A B))
(sinA(A B) cos(A-B))

Similar Questions
  1. Hi, can someone give me the answer to this question:secA-tanA=1/4. Find cosA I got: CosA=4(1-sinA) Is my answer good? Now
    1. answers icon 2 answers
  2. Hello I am having trouble with proving this:sinA/secA+secA/cscA = tan(A)(2-sin^2(A)) So far I've gotten SinA/(1/cosA) +
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions